Orbital Aspergillosis or Giant Cell Arteritis — A Diagnostic Dilemma. (March 2013) - Ali, Hassan; Lui, Nai Lee; Salkade, Parag R; Mohan, P Chandra; Lingegowda, Pushpalatha Bangalore; Tan, York Kiat
Orbital aspergillosis is an uncommon but potentially fatal disease. Its initial clinical presentation can be nonspecific and may be easily confused with other systemic diseases (such as neoplasms, other orbital infections which could include bacterial, mycobacterium and fungal infections), systemic vasculitis and other inflammatory conditions. Use of systemic corticosteroid may result in transient symptom relief further delaying the diagnosis. We describe its occurrence in a 76-year-old Chinese female with underlying rheumatoid arthritis who presented with a four-week history of left fronto-temporal headache, and ipsilateral blurring of vision with an elevated erythrocyte sedimentation rate (ESR). Although temporal artery biopsy was negative for giant cell arteritis (GCA), high-dose corticosteroids were initially started for presumptive GCA. There was an initial transient improvement in headache and in her left eye's visual acuity. However, this was followed by a worsening headache and complete visual loss in her left eye. Magnetic resonance imaging (MRI) revealed a new orbital apical mass-like lesion extending from the sphenoid sinus which was diagnosed as aspergillus infection on biopsy. Her condition improved and remained stable after the institution of appropriate anti-fungal therapy.